Chronic pain with neuropathic characteristics after surgery for major trauma to the lower limb: prevalence, predictors, and association with pain severity, disability, and quality of life in the UK WHiST trial. (1st June 2021) - Keene, David J.; Knight, Ruth; Bruce, Julie; Dutton, Susan J.; Tutton, Elizabeth; Achten, Juul; Costa, Matthew L.
Abstract : Aims: To identify the prevalence of neuropathic pain after lower limb fracture surgery, assess associations with pain severity, quality of life and disability, and determine baseline predictors of chronic neuropathic pain at three and at six months post-injury. Methods: Secondary analysis of a UK multicentre randomized controlled trial (Wound Healing in Surgery for Trauma; WHiST) dataset including adults aged 16 years or over following surgery for lower limb major trauma. The trial recruited 1, 547 participants from 24 trauma centres. Neuropathic pain was measured at three and six months using the Doleur Neuropathique Questionnaire (DN4); 701 participants provided a DN4 score at three months and 781 at six months. Overall, 933 participants provided DN4 for at least one time point. Physical disability (Disability Rating Index (DRI) 0 to 100) and health-related quality-of-life (EuroQol five-dimension five-level; EQ-5D-5L) were measured. Candidate predictors of neuropathic pain included sex, age, BMI, injury mechanism, concurrent injury, diabetes, smoking, alcohol, analgaesia use pre-injury, index surgery location, fixation type, Injury Severity Score, open injury, and wound care. Results: The median age of the participants was 51 years (interquartile range 35 to 64). At three and six months post-injury respectively, 32% (222/702) and 30% (234/787) had neuropathic pain, 56% (396/702) and 53% (413/787) had chronic pain without neuropathic characteristics, and the remainder were pain-free. Pain severity was higher among those with neuropathic pain. Linear regression analyses found that those with neuropathic pain at six months post-injury had more physical disability (DRI adjusted mean difference 11.49 (95% confidence interval (CI) 7.84 to 15.14; p < 0.001) and poorer quality of life (EQ-5D utility -0.15 (95% CI -0.19 to -0.11); p < 0.001) compared to those without neuropathic characteristics. Logistic regression identified that prognostic factors of younger age, current smoker, below knee fracture, concurrent injuries, and regular analgaesia pre-injury were associated with higher odds of post-injury neuropathic pain. Conclusion: Pain with neuropathic characteristics is common after lower limb fracture surgery and persists to six months post-injury. Persistent neuropathic pain is associated with substantially poorer recovery. Further attention to identify neuropathic pain post-lower limb injury, predicting patients at risk, and targeting interventions, is indicated. Cite this article: Bone Joint J 2021;103-B(6):1047–1054.